Model Pembelajaran Pancasila Berbasis Hybrid Learning: Studi Kualitatif Tata Kelola dan Pengalaman Belajar Nilai Mahasiswa di Era Digital - Agersi Diah Anggraini (SEMESTA: Jurnal Ilmu Pendidikan dan Pengajaran, 2026)
Pancasila Education in the digital era faces two major challenges: cyber polarization and the increasing adoption of hybrid learning. This critical qualitative case study examines pedagogical governance and the learning experiences of lecturers and students in negotiating Pancasila values within hybrid learning environments supported by a Learning Management System (LMS). Data were collected through in-depth interviews with Generation Z students, lecturers, and academic staff, participatory observation of synchronous and asynchronous learning, and institutional policy document analysis. The findings identify three key issues: (1) administrative technofetishism, where value education is reduced to quantitative LMS indicators; (2) existential alienation, in which limited face-to-face interaction weakens empathy and meaningful value internalization; and (3) ethical schizophrenia, reflected in the gap between normative compliance in LMS activities and students’ actual behavior on social media. The study concludes that current hybrid learning promotes superficial internalization of Pancasila values. It recommends reconstructing instructional practices through Value-Based Critical Digital Pedagogy emphasizing dialogic engagement, reflective learning, and authentic ethical assessment.